AIDS since 1984: No evidence for a new, viral epidemic – not even in Africa - Duesberg, Peter H.; Mandrioli, Daniele; McCormack, Amanda; Nicholson, Joshua M.; Rasnick, David; Fiala, Christian; Koehnlein, Claus; Bauer, Henry H.; Ruggiero, Marco (Italian Journal of Anatomy and Embryology, 2011)
Since the discoveries of a putative AIDS virus in 1984 and of millions of asymptomatic carriers in subsequent years, no general AIDS epidemic has occurred by 2011. In 2008, however, it has been proposed that between 2000 and 2005 the new AIDS virus, now called HIV, had killed 1.8 million South Africans at a steady rate of 300,000 per year and that anti-HIV drugs could have saved 330,000 of those. Here we investigate these claims in view of the paradoxes that HIV would cause a general epidemic in Africa but not in other continents, and a steady rather than a classical bell-shaped epidemic like all other new pathogenic viruses. Surprisingly, we found that South Africa attributed only about 10,000 deaths per year to HIV between 2000 and 2005 and that the South African population had increased by 3 million between 2000 and 2005 at a steady rate of 500,000 per year. This gain was part of a monotonic growth trajectory spanning from 29 million in 1980 to 49 million in 2008. During the same time Uganda increased from 12 to 31 million, and Sub-Saharan Africa as a whole doubled from 400 to 800 million, despite high prevalence HIV. We deduce from this demographic evidence that HIV is not a new killer virus. Based on a review of the known toxicities of antiretroviral drugs we like to draw the attention of scientists, who work in basic and clinical medical fields, including embryologists, to the need of rethinking the risk-and-benefit balance of antiretroviral drugs for pregnant women, newborn babies and all others who carry antibodies against HIV.